The formation of carbon nanofibers on powdered activated carbon impregnated with nickel. - Ahmed, Yehya M.; Al-Mamun, Abdullah; Muyibi, Suleyman Aremu; Al-Khatib, Ma'an Fahmi Rashid; Jameel, Ahmed Tariq; Al-Saadi, Mohammed A. (2009)
In the present work, the production and characterization of carbon nanofibers (CNFs) composite is reported. Carbon nanofibers (CNF) were produced on powdered activated carbon PAC—impregnated with nickel—by Chemical Vapor Deposition (CVD) of a hydrocarbon in the presence of hydrogen at ~780° C. The flow rates of carbon source and hydrogen were fixed. The CNFs were formed directly over the impregnated AC. Variable weight percentage ratios of the catalyst salt (Ni+2) were used for the impregnation (1, 3, 5, 7 and 9%, respectively). The product displays a relatively high surface area, essentially constituted by the external surface, and the absence of the bottled pores encountered with activated carbon. FSEM, TEM and TGA were used for the characterization of the product